2007
DOI: 10.2527/jas.2006-499
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations between two strains of Durocs and crossbreds from differing production environments for slaughter traits

Abstract: The aim of this study was to estimate the genetic correlations between 2 purebred Duroc pig populations (P1 and P2) and their terminal crossbreds [C1 = P1 x (Landrace x Large White) and C2 = P2 x (Landrace x Large White)] raised in different production environments. The traits analyzed were backfat (BF), muscle depth (MD), BW at slaughter (WGT), and weight per day of age (WDA). Data sets from P1, P2, C1, and C2 included 26,674, 8,266, 16,806, and 12,350 animals, respectively. Two-trait models (nucleus and comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 24 publications
3
49
2
1
Order By: Relevance
“…The mean HCW of 93.37 kg with a SD = 8.60 kg is in agreement with HCW reported by Fix et al (2010) but is somewhat higher than the final weight reported by Zumbach et al (2007) in similar crossbred populations. On average, litter had 12.1 ± 3.8 piglets born alive.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The mean HCW of 93.37 kg with a SD = 8.60 kg is in agreement with HCW reported by Fix et al (2010) but is somewhat higher than the final weight reported by Zumbach et al (2007) in similar crossbred populations. On average, litter had 12.1 ± 3.8 piglets born alive.…”
Section: Resultssupporting
confidence: 88%
“…Estimated residual variances were high compared to other variance components for each trait (0.070 for BWT, 1.000 for PWM, and 56.228 for HCW). The relatively high residual variances could be due to the variation of the Mendelian sampling, which is not included directly in the model (Zumbach et al, 2007). Therefore, the Mendelian sampling becomes part of the residual and contributes to the increasing of the estimated residual variance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production traits Heritabilities for production traits were estimated at 0.29, 0.50 and 0.41 for ADG, BF and MD, respectively, in the sire line and 0.29 and 0.42 for ADG and BF, respectively, in the dam line. Heritabilities for ADG and BF were similar to values in literature which ranged from 0.23 to 0.40 for ADG (Ferraz and Johnson, 1993;Serenius and Stalder, 2004;Rosendo et al, 2007a) and from 0.30 to 0.51 for BF Serenius and Stalder, 2004;Zumbach et al, 2007). The slightly higher heritability for BF in the sire line compared to the dam line was unexpected because breeding in the sire line primarily focused on reduction of BF, while this was of lesser emphasis in the dam line.…”
Section: Reproduction Traitssupporting
confidence: 69%
“…The slightly higher heritability for BF in the sire line compared to the dam line was unexpected because breeding in the sire line primarily focused on reduction of BF, while this was of lesser emphasis in the dam line. The heritability for MD was slightly higher than previously reported heritabilities which ranged from 0.12 to 0.31 (Hermesch et al, 2000b;Zumbach et al, 2007). Genetic and phenotypic correlations among the production traits were approaching zero in the dam line.…”
Section: Reproduction Traitsmentioning
confidence: 54%